2020
DOI: 10.1155/2020/5142797
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Combined with Tissue Fusion Technology Promoted Wound Healing in Porcine Bowel Anastomosis

Abstract: Objective. To evaluate the possible biological effect of allogenic mesenchymal stem cells (MSCs) combined with tissue fusion technology on the anastomosis. Methods. Sixteen pigs were divided into a 7 d group and 14 d group, each of which was further subdivided into an MSC-treated group and a control group. Five anastomoses per animal were established using LigaSure ForceTriad (Covidien, MA, USA), a tissue sealing system. Cell migration and tissue-specific differentiation potency, in addition to potential cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Although it has been demonstrated that endogenous MSCs contribute to tissue repair, their quantity and potency are insufficient to completely regenerate damaged tissue 14 . On the other hand, it has been proposed that transplanted MSCs are able to migrate to sites of damage and then differentiate into target cells and replace damaged tissues 15 . Therefore, researchers have been working to find exogenous MSC populations with favorable potential for migration, proliferation, and chondrogenic differentiation for cartilage regeneration.…”
Section: Role Of Mscs In Cartilage Repairmentioning
confidence: 99%
“…Although it has been demonstrated that endogenous MSCs contribute to tissue repair, their quantity and potency are insufficient to completely regenerate damaged tissue 14 . On the other hand, it has been proposed that transplanted MSCs are able to migrate to sites of damage and then differentiate into target cells and replace damaged tissues 15 . Therefore, researchers have been working to find exogenous MSC populations with favorable potential for migration, proliferation, and chondrogenic differentiation for cartilage regeneration.…”
Section: Role Of Mscs In Cartilage Repairmentioning
confidence: 99%
“…Pan et al [ 47 ] combined tissue fusion technology with allogenic ASCs in their 2020 publication. Sixteen pigs were divided in two groups related to the sacrifice date (7 or 14 d) and each group was subdivided in an ASC-treated or a control subgroup ( n = 4 each).…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, five studies[ 40 , 44 , 45 , 49 , 51 ] reported significant lower AL incidence, five[ 32 , 40 , 45 , 49 , 50 ] reported fewer adhesions, four[ 40 , 45 , 49 , 51 ] fewer abscesses and one less mortality[ 44 ]. Eight studies[ 37 , 39 , 45 , 47 - 51 ], analyzed SC labelling and confirmed SC survival in this potentially septic area.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, PCNA participates in cell proliferation by mediating DNA polymerase while blocking the PCNA production in cells severely affects cell division, which takes a significant part in the synthesis of DNA and its repair, cell proliferation, and progression of the cell cycle (77,78). Studies show treatment of MSCs could elevate the expression of PCNA, promote wound healing, and enhance re-epithelialization (79)(80)(81). Animals treated with MSCs show improving wound healing with no detectable side effects related to increasing viability, proliferation, and migration of epithelial cells (82).…”
Section: Mscs and Proliferation/migrationmentioning
confidence: 99%